Changes in haematological indices among children with sickle cell disease on hydroxyurea treatment for at least 1 year: A cohort study - Stephen Emuli; Crispus Tegu; Faith Oguttu; Ritah Nantale; Paul Ochieng; George Passi; Julian Abeso; Joan Wamulugwa; Milton W. Musaba; Ruth Namazi; Sarah Kiguli; David Mukunya (PLoS ONE, 2025)
Background Sickle cell disease is the 12 th cause of under-five mortality in Africa, with over 81,000 deaths attributed to sickle cell disease annually. Hydroxyurea is one of the few disease-modifying therapies available for the management of sickle cell disease. This study aimed to assess changes in haematological indices among children who had been initiated on hydroxyurea for at least one year in a non-trial setting at a regional referral hospital in Eastern Uganda. Methods We conducted a cohort study, which included children who attended the sickle cell clinic from 21/Aug/2024 to 30/Oct/2024. Data were analyzed using Stata version 18.0. We conducted a paired sample t-test comparing the haematological indices of children with sickle cell disease at baseline and at least one year later. Results We included 324 children. Nearly half 155/324 (47.8%) of the participants had good monthly adherence to hydroxyurea. The mean haemoglobin level at follow-up increased by 0.77g/dl (p <0.001) from 7.07g/dl (SD 0.10) at baseline to 7.84g/dl (SD 0.09). There was an increase in the mean corpuscular volume [0.97fl (p=0.645)] and mean corpuscular haemoglobin [0.58pg (p=0.120)]. The white blood cell count decreased by 6.17x10 3 /µl (p<0.001) from 20.77x10 3 /µl (SD ± 0.806) at baseline to 14.60x10 3 /µl (SD ± 0.613) at follow-up. The differential white cell counts of neutrophils, lymphocytes, monocytes, and basophils also decreased. Conclusion Hydroxyurea resulted in an increase in mean haemoglobin level and a decrease in absolute and differential white blood cell count. The benefit was more pronounced among children with good adherence to hydroxyurea. We add our voice to calls for continued advocacy for the availability of hydroxyurea for use by children with sickle cell disease in low-resource settings. We also recommend a routine complete blood count to monitor response to treatment and also guide patient management among children with sickle cell disease initiated on hydroxyurea.